Immune-related adverse events in checkpoint blockade: Observations from human tissue and therapeutic considerations - Williams, Kristian C.; Gault, Abigail; Anderson, Amy E.; Stewart, Christopher J.; Lamb, Christopher A.; Speight, R. Ally; Rajan, Neil; Plummer, Ruth; Pratt, Arthur G. (Frontiers in Immunology, 2023)
Checkpoint inhibitors (CPIs) are monoclonal antibodies which, by disrupting interactions of immune checkpoint molecules with their ligands, block regulatory immune signals otherwise exploited by cancers. Despite revolutionary clinical benefits, CPI use is associated with an array of immune-related adverse events (irAEs) that mirror spontaneous autoreactivity. Severe irAEs necessitate pausing or stopping of CPI therapy and use of corticosteroids and/or other immunomodulatory interventions. Despite increasingly widespread CPI use, irAE pathobiology remains poorly understood; its elucidation may point to targeted mitigation strategies and uncover predictive biomarkers for irAE onset in patients, whilst casting new light on mechanisms of spontaneous immune-mediated disease. This review focuses on common CPI-induced irAEs of the gut, skin and synovial joints, and how these compare to immune-mediated diseases such as ulcerative colitis, vitiligo and inflammatory arthritis. We review current understanding of the immunological changes reported following CPI therapy at the level of peripheral blood and tissue. Many studies highlight dysregulation of cytokines in irAE-affected tissue, particularly IFN and TNF-. IrAE-affected tissues are also predominantly infiltrated by T-cells, with low B-cell infiltration. Whilst there is variability between studies, patients treated with anti- programmed cell death-1 (PD-1)/PDL-1 therapies seem to exhibit CD8+ T-cell dominance, with CD4+ T-cells dominating in those treated with anti- cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) monotherapy. Interestingly, CD8+CXCR3+ T-cells have been reported to be elevated in gastrointestinal, dermatological and musculoskeletal -irAE affected tissues. These findings may highlight potential opportunities for therapeutic development or re-deployment of existing therapies to prevent and/or improve the outcome of irAEs.